Investigating Critical Effect Of China Palace Museum's Social Media Service Quality On Visitors’ Satisfaction (Journal of Namibian Studies : History Politics Culture, 2023)
Beijing is a culturally rich city with a long history, and the Palace Museum in Beijing is one of the most popular tourist destinations for visitors from both China and abroad. In recent years, with the rapid development of internet technology, social media has seen an explosive growth, and people have changed their traditional ways of traveling. By viewing short videos and other related information on social media, people's choices of travel destinations have been greatly influenced. The Palace Museum has also created official accounts on various social media platforms, and actively publishes timely tourism-related information about visiting and touring the museum. This study aims to evaluate the influence of the Palace Museum's social media presence on tourists' perceptions and behaviors. Survey research will be used to collect data from visitors who have visited the Palace Museum and used its social media accounts. The collected data will be analyzed to determine to what extent the Palace Museum's social media presence influences tourists' perceptions and behaviors during their visit. This study will help to understand the impact of social media on the tourism industry and provide insights for other cultural institutions that wish to strengthen their social media strategies.